Optimal product variety in radio markets. (27th July 2016) - Berry, Steven; Eizenberg, Alon; Waldfogel, Joel
Abstract : A vast theoretical literature explores inefficient market structures in free‐entry equilibria, and previous empirical work demonstrated that excessive entry may obtain in local radio markets. We extend that literature by relaxing the assumption that stations are symmetric, allowing for endogenous horizontal and (unobserved) vertical station differentiation. We find that, in most broadcasting formats, a social planner who takes into account the welfare of market participants eliminates 50%–60% of the observed stations. In 80%–94.9% of markets where high‐quality stations are observed, welfare could be unambiguously improved by converting one such station into low‐quality broadcasting, suggesting local overprovision of quality.